2015
DOI: 10.1186/s12889-015-1788-0
|View full text |Cite
|
Sign up to set email alerts
|

Cross-sectional associations between residential environmental exposures and cardiovascular diseases

Abstract: BackgroundPrior research examining neighbourhood effects on cardiovascular diseases (CVDs) has focused on the impact of neighbourhood socio-economic status or a few selected environmental variables. No studies of cardiovascular disease outcomes have investigated a broad range of urban planning related environmental factors. This is the first study to combine multiple neighbourhood influences in an integrated approach to understanding the association between the built and social environment and CVDs. By modelin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
58
1
3

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 69 publications
(66 citation statements)
references
References 75 publications
4
58
1
3
Order By: Relevance
“…This paper results are in agreement with several recent studies 5,7,18,19 , which show that a residential proximity of up to 150 meters to a roadway of great vehicle flow increases the risk in CD mortality. Residential proximity to traffic is a measure of indirect exposure used as a proxy of exposure to air pollutants from traffic.…”
Section: Discussionsupporting
confidence: 82%
See 1 more Smart Citation
“…This paper results are in agreement with several recent studies 5,7,18,19 , which show that a residential proximity of up to 150 meters to a roadway of great vehicle flow increases the risk in CD mortality. Residential proximity to traffic is a measure of indirect exposure used as a proxy of exposure to air pollutants from traffic.…”
Section: Discussionsupporting
confidence: 82%
“…Residential proximity to traffic is a measure of indirect exposure used as a proxy of exposure to air pollutants from traffic. It has also been used to mainly characterize the chronic exposure to these pollutants, considering the residential place might be related to continuous exposure, which would make the effects gradual on health and cumulative throughout life 7,19 . Several authors have found that chronic exposure to air pollution from vehicular traffic increases the progression and instability of atherosclerosis through inflammatory processes, thus promoting other ischemic events 4,5,18 that not only create the disease, but also enhance an existing pathological condition 4,6 .…”
Section: Discussionmentioning
confidence: 99%
“…For example, a higher density of fast-food outlets around the home was associated with fast-food purchasing frequency among adolescents in London, ON, 35 and cardiovascular disease was positively associated with fast-food outlet density among adults living in Toronto. 36 Studies were diverse in terms of study populations, sample size, design, outcomes of interest and findings by area-level exposures of interest (socio-economic status, demographic characteristics and food environment exposures) (Supplementary Table 1). …”
Section: Resultsmentioning
confidence: 99%
“…However, these disciplines have been divergent and currently operate in separate fields (Harris et al, 2016;Koohsari et al, 2013;Wernham, 2011). Yet recent literature has linked land use to a wide range of illness and death causes in developed nations, including the asthma (Son et al, 2015), high blood pressure (Langerudi et al, 2015), cancer (LopezCima et al, 2011), cardiovascular disease (Chum and O'Campo, 2015;Réquia Júnior et al, 2015), injury (Factor et al, 2013), mental disease (Barton and Pretty, 2010), obesity (Brown et al, 2009), and general health (Gascon et al, 2016;Richardson and Mitchell, 2010). Scholars have good theoretical reasons to believe the empirical linkages, since land use can shape the inhabitants' lifestyles and subsequently impacts their health (Brown et al, 2009;Heinrich et al, 2010;Wu et al, 2016).…”
Section: Introductionmentioning
confidence: 98%